UPR decreases CD226 ligand CD155 expression and sensitivity to NK cell‐mediated cytotoxicity in hepatoma cells. Issue 12 (29th October 2014) - Gong, Jiuyu; Fang, Liang; Liu, Rongrong; Wang, Ying; Xing, Jinliang; Chen, Yibing; Zhuang, Ran; Zhang, Yun; Zhang, Chunmei; Yang, Angang; Zhang, Xudong; Jin, Boquan; et al.
Abstract : NK cells play important roles in anti‐tumor immunity. CD226 is a major NK‐cell activating receptor, which transduces activating signals after binding ligands CD155 and CD112. Here, we demonstrated that activated unfolded protein response (UPR) attenuated the sensitivity of human hepatocellular carcinoma cell (HCC) to NK‐cell cytotoxicity by decreasing the expression level of CD226 ligand CD155 in HCC. The decreased expression level of CD155 was due to the involvement of the activating transcription factor 6 (ATF6) and inositol‐requiring enzyme 1α (IRE1α) pathways. In addition, the IRE1α pathway contributed to the increased expression level of the ER‐associated degradation (ERAD)‐related molecule HRD1 and facilitated the degradation of CD155. Moreover, we found that low levels of CD155 expression were significantly associated with poor prognosis in patients with HCC. Thus, our results provide molecular, cellular, and clinical evidence demonstrating a novel NK cell‐associated immune evasion mechanism, and indicate that targeting this immune evasion pathway may be meaningful in treating patients with HCC.